The effects of flooding and Phytophthora alni infection on black alder - V. Strnadová; K. Černý; V. Holub; B. Gregorová (Journal of Forest Science, 2010)
The influences of long-term flooding and Phytophthora alni subsp. alni infection on the growth and development of 4-year-old Alnus glutinosa (black alder) saplings were investigated. The black alder saplings were divided into four groups and then subjected to combinations of both factors - flooded and inoculated with pathogen, flooded non-inoculated, non-flooded inoculated, and control. The biomass of the living roots and actinorrhizae, increase in stem length, length of leaves, rate of chlorotic foliage, amount of foliage biomass and length of stem necrosis were assessed after seven weeks. Both factors, flooding and P. alni infection significantly affected the black alder. In addition, a significant effect of interaction was observed. The inoculated flooded group had a substantially lower biomass weight of living roots, actinorrhiza and leaves than the other groups. The necroses caused by the pathogen in the flooded group were more extensive than those in the non-flooded one. These findings demonstrate that the simultaneous incidence of stress caused by flooding and P. alni infection is highly dangerous for black alder.